Menstruation, Segregation and Religious Faith: A Case Study of Chhaupadi in Far Western Nepal - Duwadi, Pampha (Rural Development Journal, 2025)
This study aims to examine the cultural, social, and religious factors that contribute to the practice of Chhaupadi Pratha. Menstruation is a natural biological process that occurs to a women, typically beginning at puberty and continuing until menopause. Chhaupadi Pratha is a harmful tradition practice in rural areas of Nepal, which mandates the exclusion of women from their homes during their menstrual periods. Rooted in religious and cultural beliefs that consider menstruating women to be impure, this tradition forces women to isolate themselves in poorly constructed shelters, often lacking basic amenities such as warmth, safety, and hygiene. The practice has been linked to numerous health risks, including physical abuse, malnutrition, and even death due to exposure to harsh weather conditions or attacks by animals. Despite being outlawed in Nepal, >Chhaupadi persists due to entrenched societal norms, limited education, and resistance to change in rural communities. The continuation of Chhaupadi Pratha highlights the deeply ingrained gender inequality that persists in these regions, where women’s health, rights, and dignity are disregarded in the name of tradition.